1975
DOI: 10.1056/nejm197504242921703
|View full text |Cite
|
Sign up to set email alerts
|

Function of the Male Sex Organs in Heroin and Methadone Users

Abstract: The function of the secondary sex organs was found to be markedly impaired in 29 participants in a methadone maintenance program. The ejaculate volume and seminal vesicular and prostatic secretions were reduced by over 50 per cent in methadone clients, as compared to 16 heroin addicts and 43 narcotic-free controls. Serum testosterone levels were also approximately 43 per cent lower in methadone clients than in controls or heroin users. Although the sperm count of methadone clients was more than twice the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
1
4

Year Published

1976
1976
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(86 citation statements)
references
References 11 publications
4
77
1
4
Order By: Relevance
“…Thus, again it seems to be mainly an impairment of the pulsatile component of LH secretion that occurs in response to the sustained stress of prolonged critical illness (56). Endogenous dopamine, opiates and the elevated estradiol levels (3) may be involved in the pathogenesis of hypogonadotropism, as exogenous dopamine, opioids and estrogens may further diminish blunted LH secretion (56,78).…”
Section: Luteinizing Hormone±testosterone Axismentioning
confidence: 99%
“…Thus, again it seems to be mainly an impairment of the pulsatile component of LH secretion that occurs in response to the sustained stress of prolonged critical illness (56). Endogenous dopamine, opiates and the elevated estradiol levels (3) may be involved in the pathogenesis of hypogonadotropism, as exogenous dopamine, opioids and estrogens may further diminish blunted LH secretion (56,78).…”
Section: Luteinizing Hormone±testosterone Axismentioning
confidence: 99%
“…Moreover, other studies have suggested that monocytes provide soluble Fas, which has the potential to trigger lymphocyte apoptosis (9) . Whereas (10) provides further support for the hypothesis that morphine may be directly compromising immune function by enhancing apoptosis of T lymphocytes in patients with heroin addiction through alteration of BCl2 and BAX genes expression.Some studies demonstrated that high-dose methadone was shown to depress plasma testosterone levels (11,12) , and other clinical studies have reported decreased sexual drive and performance in male heroin addicts (13) . This study is designed for better understanding of the underlying mechanisms of heroin-induced toxicity which may allow more informed application of opioid replacement therapy as well as the development of additional novel therapeutic interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Cicero et al (9) reported that a 3 day implantation of morphine pellets in male rats produced atrophy of the male accessory reproductive organs and low plasma testosterone levels. Our experimental design differs from Cicero's experiment in that we used rats which were fully mature sexually and were administered morphine repeatedly for a longer period of time.…”
Section: Discussionmentioning
confidence: 99%